TRADISI RITUAL SEBLANG DALAM PERSPEKTIF HUKUM ISLAM DI DESA OLEHSARI KECAMATAN GLAGAH BANYUWANGI - Muhammad Jufri; Zulham Nur Hali (LP2M Universitas Ibrahimy, 2017)
Seblang dance is a tradition practiced by some communities Banyuwangi that has value and a purpose, namely as a place of religious expression, as a belief system that aims to find a relationship with the spirit world. Some of the values contained in the Seblang dance tradition has a good purpose is certainly not contrary to the teachings of Islam as well.